Metabolic imaging with cardiac magnetic resonance spectroscopy - Neubauer, S (2009)
The only non invasive technique for the assessment of cardiac metabolism in patients that does not use radiation is magnetic resonance spectroscopy (MRS). By interrogating signals from phosphorus-31 and hydrogen-1, spectroscopy offers a wealth of metabolic information on the heart muscle. This review focuses on the two areas of greatest potential for MRS: heart failure and ischemic heart disease. MRS has demonstrated deranged cardiac energetics in patients with heart failure, and this is probably a major mechanism contributing to contractile dysfunction. In ischemic heart disease, altered energetics are a highly sensitive indicator of the presence of myocardial ischemia, offering the prospect of a non invasive biochemical stress test for the heart. Although major technical development is required for the future, cardiac MRS holds great potential for clinical application.